Strategic Perturb and Observe Algorithm for Partial Shading Conditions - Muhammad Mateen Afzal Awan (Sir Syed University Research Journal of Engineering and Technology)
Solar photovoltaic (PV) is the cheapest renewable resource of electrical energy. Its dependence on the connected load bounds its production capability. To deliver the determined power, it is required to operate at the maximum power point (MPP) in the characteristic curve of the PV array. Tracking the MPP requires electronic circuits govern by MPP tracking (MPPT) algorithms. The most simple, cheap, and softly implementable MPPT algorithm is “Perturb and Observe (P&O)”. It efficiently performs under uniform weather conditions (UWC) but fails under partial shading conditions (PSC) due to the formation of multiple peaks in the P-V characteristic curve of a PV cell. In this paper, weaknesses of the P&O algorithm are studied and overcome by structural modifications. The proposed structure is named the “strategic P&O algorithm”. Performance of the conventional and proposed algorithms is evaluated at the following standard benchmarks, tracking speed, tracking time, efficiency, and ability to track the GMPP under PSC. Results have shown that the proposed SP&O algorithm has outperformed the conventional P&O algorithm under numerous weather conditions. Simulations are performed in MATLAB/Simulink.